An active solar water wall for passive solar greenhouse heating. (15th February 2022) - Xu, Weiwei; Guo, Huiqing; Ma, Chengwei
Graphical abstract: Highlights: A low-cost active solar water wall was designed for greenhouse heating. Hollow polycarbonate sheet formed water wall with active solar heat management. Daily average heat collection on the basis of floor area was 0.83 MJ m −2 . Minimum air temperature in Chinese solar greenhouse rose by 3.3 °C in coldest days. Chinese solar greenhouse with water wall enabled warm-season crops' winter planting. Abstract: A high thermal capacity north wall is essential for nighttime heating of Chinese solar greenhouses. However, thermal storage ability of the north wall using regular building materials is limited because of their slow heat conduction restricting heat transfer from wall surface to the depth. This study added an active solar water wall constructed of hollow polycarbonate sheets to the north wall, supplemented by an underground water storage tank, to increase nighttime temperature. To evaluate water wall's thermal effect, a field test was conducted, as well as a theoretical verification. Its performance was evaluated in terms of solar heat collection and release capability, nighttime temperature increase and thermal performance in adverse weather. During the 22 coldest days of winter in Beijing, daily averages of collected heat and heat release rate on the basis of floor area were 0.83 MJ m −2 and 22.6 W m −2, respectively. Average heat-collecting efficiency reached 85.8%, and 80.4% of the collected heat was released for greenhouse heating. Compared to the scenario without the water wall, minimum nighttime air temperature increased by 3.3 °C on average. In particular, nighttime temperature maintained above 6.9 °C that was 4.1 °C higher than that in the control greenhouse during three consecutive overcast days. Retrofitting the water wall into Chinese solar greenhouses can make warm-season crop production feasible throughout winter by eliminating supplemental heating. Besides, the water wall-based system can be a self-contained solar heating system, also suitable for traditional greenhouses. Thermal analysis and economic evaluation show considerable practical application prospects.